Role conflict, role ambiguity and job stress in police officers - Zulkafaly, Fatimah; Kamarudin, Kamarulzaman; Md Hassan, Nurul Huda (2017)
Purpose - The general aims of this study were to identify the relationship between role conflict and job stress in police officers; (ii) to identify the relationship between role ambiguity and job stress in police officers; (iii) to validate the positive relationship between role conflict and role ambiguity on the job stress in police officers.Judeh (2011) argued that no existence of consensus related to organizational factors that lead to job stress in police settings. A little studies to the job stress issues in police officers in Southern Asia and Malaysia area (Masilamani et. al., 2013). According to Wong (2003), political factors, differences in practice and theory, conservative organizational settings and the need to protect confidential information are the constraints that researchers encounter in conducting study in police settings.Role conflict and job stress has a significant positive relationship (Quarat-ul-ain, Khattak & Iqbal, 2013). Role conflict and role ambiguity lead to job stress (Idris, 2011; Muchinsky, 2000).Role conflict contributed to 41% to job stress (Hsu et al., 2010).Role ambiguity plays a significant role in reducing job stress (Ramadan; 2013).The evaluation of threats, barriers and challenge were different and closely related to role conflict and job stress (Tuckey, Searle, Boyd, Winefeld & Winefeld, 2015). The clash of role conflict and ambiguity caused wrong doing in police officers (Yesiltas; 2014; Cooper, 2012). The main result of this study summarized that there is a significant relationship between role conflict and ambiguity to job stress in police officers Methodology - The study sample was comprised of 280 police officers from several contingents using purposive sampling process due to the constraint to access the particular sample and private confidential that practiced by police. A questionnaire was used to collect the data consisted of role conflict and ambiguity issues developed by Rizzo et al. (1970). The second part was to measure job stress variable using Depression Anxiety Stress Scale (DASS 21) presented by Lovibond and Lovibond (1995). Analysis data was used Partial Least Square – Structural Equation Modelling (PLS-SEM).